Letter from Campbell Morfit to James Curtis Booth, May 8, 1855 - Morfit, Campbell (1855)
Campbell Morfit (1820-1897), a distinguished chemist from the United States and co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry, writes to philosophize on the death of his wife, Marie, and request a loan from Booth of $160.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897